Chinese University Students’ Perceptions of Facilitation Strategies, Learning Motivation, and Satisfaction in Cloud-Based Virtual Classrooms - Wang, Rong; Han, Jiying; Gao, Chao; Liu, Chuanyong (Frontiers in Psychology, 2021)
This study investigated university students’ perceptions of facilitation strategies, learning motivation, and satisfaction, and the relationships between them in a cloud-based virtual classroom in mainland China. The results of an online questionnaire survey from a sample of 7,210 university students showed that students perceived high levels of facilitation strategies, learning motivation, and satisfaction. Students’ demographic characteristics, such as discipline, university type, gender, and grade, did not significantly affect their perceptions of facilitation strategies and learning outcomes. Instructor-student interaction and instructor innovation were positively related to student learning motivation and satisfaction whereas the relationships between student interaction and learning motivation and satisfaction were weak and had no practical meaning. The findings of this study have implications for creating more effective synchronous online learning environments and achieving desirable learning outcomes.